Spirituality and sustainability: experiences of the International Islamic University Malaysia - Moten, Abdul Rashid (IIUM Press, International Islamic University Malaysia, 2020)
The International Islamic University Malaysia has, since 2018, redoubled its struggle to restore its wisdom, strengths, and dignity and promote comprehensive excellence. Hence, the University adopted the United Nations’ sustainable development agenda as a complement to the University’s vision and mission of Islamisation, Integration, Internationalisation and Comprehensive Excellence.